Power quality improvement of electrical power systems within more electric aircraft - Wang, Cheng (2021)
The application of more-electric aircraft concept will see a significant increase of electrical power demands with newly developed electrical loads. This will make it essential to extract electrical power from both high-pressure and low-pressure shafts of an aircraft engine for future aircraft. With each shaft driving one electrical generation subsystem, an advanced dual-channel power generation system can be formed. The dual-generation architecture can significantly reduce the fuel assumption of aircraft engines through power transfer between different engine shafts. In such a system, two permanent magnet synchronisation generators (PMSGs) will supply a common DC bus through their dedicated AC-DC converters. On the load side, a significant penetration of power electronics is foreseen as they are essential elements to interface load and the DC bus. With an increased number of power electronic converters, harmonics from these converters will impose significant power quality challenges to the electric grid. A capacitor is required to filter the switching harmonics in the DC bus to ensure that its voltage is within the required range. However, due to a high current rating, this capacitor will be bulky and heavy. This thesis aims to address the power quality issues for the common DC bus electrical power system architecture considering a dual-channel power generation system. To improve the power quality on the DC bus, switching harmonic component cancellation schemes are proposed for different cases. In the first case, two PMSGs are considered to supply the DC bus through AC/DC converters. In this case, the modulation scheme (either SPWM or SVPWM) of one AC-DC converter is controlled to actively cancel one specific harmonic component on the DC bus. After the first case study, the use of a bidirectional buck-boost DC-DC converter as a harmonic absorber with the proposed equal-gate-width (EGW) modulation scheme is considered. The proposed method allows for the active control of the magnitude and phase angle of some specific harmonic component and thus can be used to suppress the required harmonic component on the DC bus. Simulation and experimental results have demonstrated the high robustness and effectiveness of the proposed methods.